Летрозол подовжує виживаність без прогресування в постменопаузальних хворих на розповсюджений рак молочної залози при терапії пегільованим ліпосомальним доксорубіцином у комплексі з магнітотермією - Loboda, A.; Movchan, O.; Smolanka (Sr), I.; Dumanskyi, Yu.; Lyashenko, A.; Ivankova, O.; Dosenko, I. (PH Akademperiodyka, 2025)
Background. Resistance of the advanced breast cancer (aBC) to hormone therapy and chemotherapy due to hyperactivated PI3K-pathway caused by mutations in the PIK3CA gene is a major treatment problem. Combining pegylated liposomal doxorubicin (PLD) with mild magnetothermy (MT) and letrozole could improve the efficacy of treatment. The aim was to assess the effect of combined treatment with PLD, MT, and letrozole on the survival of patients with luminal B postmenopausal aBC with mutations in the PIK3CA gene. Material and Methods. The aBC postmenopausal patients who progressed on a cyclin-dependent kinase 4/6 inhibitor (CDK4/6i) and an aromatase inhibitor (AI) or neoadjuvant chemotherapy (ACT) were included in the study. Group 1 included 20 patients, treated with PLD + MT every 28 days (4 courses) and letrozole (daily per os, 4 months). Group 2 included 20 patients, who received the same treatment without letrozole. By PIK3СА status, each group included 10 patients with a mutant PIK3СА and 10 patients with a wild-type gene. Results. Application of PLD + MT in combination with letrozole demonstrated improved progression-free survival (PFS) compared to PLD + MT alone. In group 1, the median PFS was 10.6 months (95% CI, 7.4—11.9 months) compared to a median PFS of 8.9 months (95% CI, 6.1—9.7 months) in group 2 (p = 0.005). In the sensitivity analyses, PFS of patients with wild-type PIK3CA in the first cohort was 10.1 months (95% CI, 8.7—11.1 months) compared to 8.4 months (95% CI, 7.0—10.4 months) in groups 1 and 2 respectively (p = 0.004), by 1:1 greedy nearest neighbor matching. Conclusion. PLD with local MH in combination with letrozole was more effective irrespective of the PIK3CA gene status in postmenopausal aBC patients.